REORIENTASI KEBIJAKAN KRIMINAL DALAM MENYELESAIKAN KASUS RINGAN (DARI DUE PROCESS MODEL KE REINTEGRATIVE MODEL) - S Sahabuddin (Faculty of Law, Universitas Jenderal Soedirman, 2014)
Law enforcement venial cases in Indonesia has caused many problems and criticism since the system is more concerned with the fulfilment of the administration of justice through the strict procedure than to provide substantive justice. Therefore, it is important to conduct a reorientation on crimi-nal policy by proposing a new model of resolution outside the system as an alternative way which is believed to be able to resolve the issue proportionally, as well as to restore the relationship between the related parties. Key words: venial cases, criminal justice system, reintegrative model